Development of the model of external control of quality indicators of electronic courses - Shifrin Boris; Eliseev Igor; Sokolova Viktoriia; Voinash Sergey; Zagidullin Ramil; Akhmetshin Stanislav; Meshkov Sergey (ITM Web of Conferences, 2024)
This article presents an analytical survey of internationally accepted samples for the assessment of online courses. By reviewing existing practices from around the world, the article identifies common approaches and methodologies used to evaluate the quality of electronic courses. This approach utilizes a combination of simple numeric values and fuzzy linguistic variables, which are then aggregated using fuzzy logic. This combination of numeric values and linguistic variables allows for a more comprehensive assessment of electronic courses. It takes into account both quantifiable factors, such as completion rates or assessment scores, as well as subjective factors, such as user satisfaction or engagement levels by utilizing fuzzy logic, the proposed approach is able to handle the inherent uncertainty and subjectivity in some of these indicators. The proposed approach aims to provide a more robust and accurate evaluation of the quality of electronic courses. It builds upon internationally accepted samples and incorporates a combination of objective and subjective indicators, using fuzzy logic to handle the varying degrees of uncertainty. This approach can contribute to the development of a standardized and comprehensive system for assessing the quality of electronic courses.